JAVANESE PHILOSOPHY “MANUNGGAL ING KAULA ALIT” AS A MEANS TO ERADICATE CORRUPTION - Beni Darmawan (Association of Certified Fraud Examiners Indonesia Chapter, 2018)
Corruption has a very severe impact on economic stability and state governance. Corruption means stealing the rights of community and is included as a crime that hurts many parties, especially lower or marginal communities. In Indonesia, corruption has been entrenched in society and carried out systemically. At present corruption has spread widely in all aspects of life. Corruption must be handled seriously and thoroughly, otherwise this can have a damaging impact on several aspects. One of the factors that drive the proliferation of acts of corruption is the weak control and lack of community involvement. The involvement of community is usually only in terms of reporting and complaints. Javanese philosophy ”manunggal ing kawulo alit” which means mingling with lower or marginal communities is expected to be one of the ideal solutions to prevent and eradicate corruption in Indonesia. There are many projects that can be developed to directly involve the younger generation and officials to mingle with lower communities. Living together with rural or marginal people will be able to change the nature and personal character of individuals so that they will feel guilty and have desire to change the lives of rural or marginal communities to be better.